The Link Between Green Human Resource Management and Environmental Performance through Green Innovation Practices: A Mini Literature Review During Year 2019-2023 - Marditama, Theresia; Yusliza, Mohd Yusoff; Purnomo, Albert Kurniawan (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
This article emphasizes the significance of incorporating green innovation and green human resource management (GHRM) practices in organizations to achieve long-term sustainability and environmental goals. It presents a summary of twenty peer-reviewed journal articles on green environmental performance, green innovation practices, and GHRM. The findings indicate that proactive environmental strategies, such as pollution reduction and sustainable development, have a positive impact on environmental performance. Improving sustainability and environmental performance requires green innovation. Green innovation is the process and product innovation achieved via improved production techniques and product design. Organizations should prioritize environmental friendliness and sustainability because both developed and developing countries face numerous pressing problems. Both higher management and academia will be impacted by the study. The results will assist company management in developing a green innovation process and product culture.The article also highlights the need for further research on the relationship between green innovation, GHRM, and sustainable performance in different contexts and industries.